Customers’ Interpretations of Drivers’ Nonverbal Communication in Ride-Hailing Services: A Phenomenological Study - Zidane Ahmad Busthomi; Annisa Atha Hanifah; Indra Prawira (INJECT (Interdisciplinary Journal of Communication), 2026)
Interactions between drivers and customers in online transportation services are often brief and without verbal communication. In these brief interactions, nonverbal communication becomes a crucial element in influencing customer experience (Avi, 2023). This study aims to examine how customers interpret the experience of encountering nonverbal communication forms conveyed by drivers, such as facial expressions, body gestures, tone of voice, and posture. Using a qualitative approach and the phenomenological study method of Interpretative Phenomenological Analysis (IPA), data will be collected through semi-structured interviews with 10 active user informants in the Greater Jakarta area who were recruited purposively. The results show that nonverbal elements are interpreted ambivalently and situationally. This study presents a critical dialogue on the simplistic Albert Mehrabian 7-38-55 rule by presenting the results of non-deterministic emotional interpretations.